1998
DOI: 10.1111/j.1399-0039.1998.tb03043.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of HLA class II alleles among Spanish patients with pemphigus vulgaris

Abstract: Twenty-six unrelated Spanish Caucasian individuals affected by pemphigus vulgaris (PV) were HLA typed and frequencies compared with those of 200 ethnically matched healthy controls. Twenty-three out of 26 patients were HLA-DR4. The frequency of HLA-DR14 was also increased (31%; controls: 4%). Of the 23 patients positive for HLA-DR4, 21 carried the DRB1*0402 allele. Therefore, the frequency of HLA-DRB1*0402 among patients was 81% (4% in controls; P=4.7x10(-27), OR=100.8). Interestingly, HLA-DR13, a frequent HLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0
9

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 20 publications
8
44
0
9
Order By: Relevance
“…Our results confirm previous reports showing a strong association of PV with DQB1*0503 which is in linkage disequilibrium with DR14 alleles [3,4,5,8,10,12,13,14,15,16,17]. Since the DQB1*0503 PV patients had various DRB1*14 related alleles, one alternative The AA residues are shown using the letter code.…”
Section: Pemphigus Vulgarissupporting
confidence: 92%
See 3 more Smart Citations
“…Our results confirm previous reports showing a strong association of PV with DQB1*0503 which is in linkage disequilibrium with DR14 alleles [3,4,5,8,10,12,13,14,15,16,17]. Since the DQB1*0503 PV patients had various DRB1*14 related alleles, one alternative The AA residues are shown using the letter code.…”
Section: Pemphigus Vulgarissupporting
confidence: 92%
“…The increased frequency of DRB1*0402 corroborates previous studies in Ashkenazi Jewish patients [2] and in non-Jewish Caucasians [3,4,5,6,10]. The DRB1*1401 or 1404 alleles were found associated with PV in non-Jewish patients of European ancestry (Italy, Sardinia, Spain, Boston area) [3,4,5,6] and in Asian populations (India, Pakistan, Japan) [12,13,14,15,16,17].…”
Section: Drb1supporting
confidence: 89%
See 2 more Smart Citations
“…Gonzá lez-Escribano et al 16 found that among Spanish patients with PV, HLA DR4 allele was high and HLA DR14 frequency was also increased. Interestingly, HLA DR13, a frequent HLA DR specificity in the Spanish general population, was absent among the PV patients.…”
Section: Discussionmentioning
confidence: 99%